Factors influencing return to work after stroke: the Korean Stroke Cohort for Functioning and Rehabilitation (KOSCO) Study. Issue 7 (11th July 2019) - Han, Junhee; Lee, Hae In; Shin, Yong-Il; Son, Ju Hyun; Kim, Soo-Yeon; Kim, Deog Young; Sohn, Min Kyun; Lee, Jongmin; Lee, Sam-Gyu; Oh, Gyung-Jae; Lee, Yang-Soo; Joo, Min Cheol; et al.
Abstract : Objective: To investigate the rate of return to work and identify key factors associated with return to work between 3 months and 2 years after stroke. Design: Prospective cohort study. Setting: The Korean Stroke Cohort for Functioning and Rehabilitation (KOSCO) in Korea. Participants: A total of 193 persons with first-ever stroke who reported working status at 3 months after stroke. Outcome measures: Data on baseline characteristics were collected from medical records. Functional assessments were performed using the National Institutes of Health Stroke Scale, the modified Rankin Scale, the Fugl-Meyer Assessment, the Functional Ambulatory Category, the Korean Mini-Mental State Examination, the Korean version of the Frenchay Aphasia Screening Test, the American Speech-Language-Hearing Association National Outcomes Measurement System, the Korean-Modified Barthel Index, the Geriatric Depression Scale-Short Form and the EuroQol-5 dimensions. An enumeration survey included the Reintegration to Normal Living Index, the Psychosocial Well-being Index-Short Form (, the Family Support Index and the Caregivers Burden Index. Results: Overall, 145 (75.1%) patients who had a stroke in the "Continuously-Employed" group and 48 (24.9%) in the "Employed-Unemployed" group returned to work between 3 months and 2 years after stroke. Multivariate logistic analysis demonstrated that in patients who had a stroke, characteristics such as age, PWI-SF Score, and caregiver characteristics, including age, sex (female) and living arrangements, were significantly associated with return to work between 3 months and 2 years after stroke. Conclusion: Age and PWI-SF Score of patients who had a stroke, as well as the age, sex and living arrangements of caregivers, are key factors influencing the return to work after stroke. Trial registration number: NCT03402451 .